(untitled) (Journal of the Bangladesh Agricultural University, 2017)
This study described the comparison of different physicochemical parameters between fresh and frozen lamb meat. The pH measurement for fresh and frozen lamb meat did not show a significant difference. CIE L*a*b* (Commission Internationale de l’éclairage) color measurement technique was used and ∆E (distance between 2 colors) was found 5.32. On shrinkage measurement, there were significant differences (p<0.05) between the fresh and frozen meat. Frozen lamb sample showed 26.99% shrinkage compared to the fresh lamb which showed 18.09% shrinkage. The thawing loss did not show any significant difference. For texture analysis force and work were evaluated together for both fresh and frozen samples through Warner Bratzler texture analysis. The values did not show any significant difference. The absolute values of force and work were significantly different (p<0.05). Water binding capacity of the frozen and fresh sample were 56.57% and 59.27%, respectively. The moisture contents of fresh and frozen sample were 73.64% and 72.85%, respectively. Fat contents of fresh and frozen sample were 5.08% and 6.09% respectively. The study concludes that while comparing fresh and frozen lamb, only shrinkage and texture analysis showed significant difference whereas other physicochemical properties showed minor differences. J. Bangladesh Agril. Univ. 15(2): 281-288, December 2017